Możliwości wykorzystania wybranych teorii decyzji do szacowania wartości informacji ex ante - Cypryjański, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Estimation of information value prior to knowing their content is a serious problem. This article analyzes the problem from the decision theory perspective, trying to answer two questions: value of what type of information does decision theory enable to evaluate? and what are the conditions of applying decision theory? (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 85-94